Variation in the vitamin D receptor gene is not associated with risk of colorectal cancer in the Czech Republic - Hughes, David J; Hlavatá, Ivona; Soucek, Pavel; Pardini, Barbara; Naccarati, Alessio; Vodickova, Ludmila; Jenab, Mazda; Vodicka, Pavel (Journal of gastrointestinal cancer, 2011)
PURPOSE: Increased levels of vitamin D may protect against colorectal cancer (CRC) development and recurrence. Accumulating epidemiologic evidence suggests these effects may be partly mediated by genetic variants of the vitamin D receptor (VDR) proposed to be associated with altered risk of CRC. We wished to determine if common VDR polymorphisms affected CRC risk in the Czech Republic, a homogenous European population with a high CRC incidence rate. METHODS: Frequencies of the common VDR gene polymorphisms rs2238136, rs1544410 (BsmI), rs7975232 (ApaI), and rs731236 (TaqI) were determined using allele-specific PCR in a case control analysis of a series of 754 CRC patients and 627 patients without malignant disease recruited from centers throughout the Czech Republic. Unconditional logistic regression was used to calculate odds ratios and 95% confidence intervals for the association between these variants and risk of CRC. RESULTS: None of the four polymorphisms tested had any significant effect on CRC risk. No significant differences were observed in susceptibility when the population was stratified by anatomical sub-site, sex, BMI, smoking, alcohol, or presence of polyps. CONCLUSIONS: We conclude that common variation in the VDR gene had little effect on its own on predisposition to sporadic CRC in the Czech population.
Keywords: receptory kalcitriolu; kolon; polymerázová řetězová reakce; Male; kolorektální nádory; Rectum; Risk Factors; polymorfismus genetický; prognóza; Česká republika; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; rektum; vitamin D; Polymorphism, Genetic; Czech Republic; senioři nad 80 let; lidé; ženské pohlaví; studie případů a kontrol; Humans; Receptors, Calcitriol; Colon; rizikové faktory; Aged, 80 and over; DNA; Colorectal Neoplasms; Prognosis; Polymerase Chain Reaction; Vitamin D; Female; lidé středního věku; Middle Aged